THE CIRCULAR ECONOMY APPROACH FOR THE REGENERATION OF TORRE ANNUNZIATA PORT AREA - Angrisano, Mariarosaria; Fusco Girard, Luigi (BDC. Bollettino Del Centro Calza Bini, 2017)
The UNESCO Recommendation on Historic Urban Landscape (HUL) calls for the identification of innovative models for cultural heritage conservation/regeneration. The aim of this paper is to demonstrate how new models of the circular economy can restore cities identity, increasing the tangible and intangible values of the built heritage and reducing the costs of urban renewal. This theory is reinforced on the one side through some case studies and on the other side by an applicative case study. It concerns the regeneration of Torre Annunziata port area, a historic city in Southern Italy, endowed with a suggestive cultural and landscape heritage. Keywords: Historic Urban Landscape, circular economy, waterfront regeneration